Study of the Factor Structure of Motor Fitness in 8-Year-Old Boys During the Process of Mastering the “Kin Geri” Kick Technique - Marchenko, Svitlana (Physical Education Theory and Methodology, 2025)
Objectives. The research aims to identify the factor structure of motor fitness in 8-year-old boys during the process of mastering the “Kin geri” front kick technique. Materials and methods. Thirty-two 8-year-old boys participated in the study. Both the children and their parents were informed about the nature of the research and provided written consent for participation. Participants were assured of their right to withdraw from the study at any time without explanation. All procedures were conducted following the Declaration of Helsinki. The following research methods were employed: analysis of scientific and methodological literature, pedagogical observation, timing of educational tasks, motor fitness testing, and statistical data analysis. Results. Factor analysis identified six factors accounting for 73.98% of the total variance. The largest contribution (24.87%) to the total variance of the sample was made by the factor “special complex coordination preparedness”. The second most significant factor was the “level of special motor fitness”(15.71%). Other identified factors included “physical development” (12.74%), “coordination of movements” (9.04%), “agility” (6.05%), and “flexibility” (5.58%). Since the “Kin geri” kick is executed below belt level (“Gedan” level), the contribution of flexibility is minimal and may be considered less relevant. During the training of the “Kin geri” front kick, the most influential elements include anthropometrical indicators, speed of integral movements, special coordination fitness, balance, static strength, general endurance, and the degree of technical mastery of the “Kin geri” front kick demonstrated through a series of training tasks. Conclusions. The analysis of the factor structure of motor fitness provides essential data for optimizing the training process of the “Kin geri” front kick in 8-year-old karate athletes. The findings highlight the integrity of motor skill formation and the development of motor abilities. A significant outcome of the factor analysis is the establishment of a foundation for designing effective training programs tailored to the physical development and motor fitness level of children and adolescents.